Mitigating inequality higher education research, policy, and practice in an era of massification and stratification - Teranishi, Robert T. (Advances in education in diverse communities ;, 2015)
Now more than ever, the issue of access to higher education for all is a matter of global importance. As colleges and universities worldwide increasingly extend their academic programs abroad, develop internationally mixed research teams and create international curricular initiatives, it is essential to ensure that equitable access to a high quality education remains a key component of the research and policy agenda transnationally. In this book, leading scholars from around the globe offer the most current knowledge about postsecondary access and success, offering fertile ground for new directions in higher education. A critical read for scholars, practitioners, and policymakers, this book offers interdisciplinary perspectives on key priorities and action steps for the higher education community to help mitigate economic, social, and political inequality.